PEM Fuel Cells: materials ageing and degradation - Silva, R. A. (2010)
As fuel cell technology matures and time scale to commercialization decreases, the need for a more comprehensive knowledge of materials ageing mechanisms is essential to attain specified lifetime requirements for applications. In this work, the membrane-electrode assembly (MEA) degradation of an eight cell PEM low power stack was evaluated, during and after fuel cell ageing in extreme testing conditions. The stack degradation analysis comprised observation of catalytic layer, morphology and composition. Cross sections examination of the MEAs revealed thickness variation of catalytic layer and membrane. Other modes of degradation such as cracking,